Política econômica emergencial orientada para a reduç\~ao dos impactos da pandemia da Covid-19 no Brasil: Medidas fiscais, de provis\~ao de liquidez e de liberaç\~ao de capital - Mauro Santos Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This text for discussion presents an exploratory analysis of the main measures of emergency economic policy adopted by the federal government of Brazil within the scope of the strategy to face the economic, social and public health crisis resulting from the Covid-19 pandemic. The objective is to identify, systematize and analyze the main axes of extraordinary actions instituted at the federal level in the initial phase of the crisis, a period corresponding to the four-month period March-June 2020. The strategy of extraordinary economic policy is organized into two large sets of measures, one of a fiscal nature, aimed at guaranteeing family income, supporting companies and providing financial assistance to states and municipalities, and the other related to policies for the provision of liquidity and release of regulatory capital, aimed at the stability of the financial system and the expansion of the credit supply. The scenario imposes the need to define a public sector financing strategy capable of maintaining the execution of extraordinary fiscal policy measures throughout the crisis period and ensuring the sustainability of public debt in the long run, in an inclusion-oriented economy social and economic growth.
Keywords: H12; H53; H81; P5; P16; 330; economic policy; fiscal policy; public spending; fiscal governance; Covid-19